USE OF ULTRASOUND EXAMINATION AS A METHOD OF DIAGNOSIS OF PATHOLOGIES OF THE HEPATOBILIARY SYSTEM OF SMALL ANIMALS - Kyrychko, B.; Zvenihorodska, T. (Scientific Progress & Innovations, 2022)
The liver of small domestic animals is most often exposed to pathological effects. Poor-quality feed, unbalanced nutrition, use of various drugs can negatively affect the hepatobiliary system of animals. 36 dogs and 54 cats aged from 6 months to 17 years were selected for the research based on the researcheducational-production clinic of Poltava State University. The animals were observed from January 2021 to January 2022. In experimental animals, clinical signs were recorded: ictericity of mucous membranes, vomiting, exhaustion, unpleasant odour from the skin and the oral cavity, frequent diarrhea, or constipation. Preparation of the animals included a 10-hour fasting diet. Ultrasound examination was performed in Bmode. The acoustic window was prepared by shaving the area from the xiphoid cartilage to the navel, in dogs the area of the last two intercostal spaces was additionally shaved. It was found that 58.3 % of dogs had concomitant diseases: heart failure – 14.3 %, chronic renal failure – 28.5 %, alimentary obesity – 10.3 %, while the number of concomitant diseases was much lower in cats: 12.5 % had chronic renal failure, heart failure – 6.2 %, dietary obesity – 6.2 %. It was found that the most common pathologies of the hepatobiliary system of dogs are hepatosis and hepatitis; in cats – liver lipidosis and cholangiohepatitis. Among dog breeds, Yorkshire terriers, Pekingese, and Chihuahuas are most prone to diseases of the hepatobiliary system, while cats have no breeding predisposition. The average age of cats with liver lipidosis is 6.2 years, females are most prone (75 % of those examined). Signs of hepatosis in dogs on an ultrasound scan include rounding of the edges of the liver, increased echogenicity of liver tissues, fine-grained and coarse-grained echostructure, and an increase in the size of the liver. Signs of liver lipidosis in cats are the rounding of the edges of the liver and its increase, increased echogenicity of liver tissues, and a blurred, smoothed pattern.